Faktor-Faktor Yang Berhubungan Dengan Kejadian Bullying Di Smpn 6 Kota Payakumbuh Tahun 2024 - Miranda Putri, Nadia; Putri, Marizki; Prima, Rezi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
The phenomenon of bullying has been going on for a long time throughout the world and is endless. Bullying can result in short-term and long-term effects on both victims, perpetrators and witnesses The purpose of this study was to determine the factors related to bullying incidents in class VIII students at SMP N 6 Payakumbuh City in 2024. This study used a quantitative approach with a correlation method. The sampling technique used a simple random sampling technique with a sample analysis of 64 respondents. The data was obtained on April 4, 2024, then the research was conducted on July 17-19, 2024 by having respondents fill out the questionnaire provided. The results of the chi-square statistical test showed that the family support factor with the incident of bullying p-value 0.012, the peer group factor with the incident of bullying p-value 0.028, the self-concept factor with the incident of bullying p-value 0.037 where the support of family factors, peer groups, and self-concept obtained p-value <0.05), which means there is a significant relationship between family support factors, peers, and self-concept with the incident of bullying in class VIII students at SMP N 6 Payakumbuh City in 2024 With the conclusion obtained low family support, high peer groups and low self-concept, then bullying incidents will often occur. For this reason, it is hoped that teachers can increase bullying prevention activities, and students can further identify the factors that cause bullying incidents in schools.